Thermally Crosslinked Hydrogen-Bonded Organic Framework Membranes for Highly Selective Ion Separation - Xiyu Song; Chen Wang; Xiangyu Gao; Yao Wang; Rui Xu; Jian Wang; Peng Li (Molecules, 2023)
The weak bonding energy and flexibility of hydrogen bonds can hinder the long-term use of hydrogen-bonded organic framework (HOF) materials under harsh conditions. Here we invented a thermal-crosslinking method to form polymer materials based on a diamino triazine (DAT) HOF (FDU-HOF-1), containing high-density hydrogen bonding of N-H⋯N. With the increase of temperature to 648 K, the formation of –NH– bonds between neighboring HOF tectons by releasing NH3 was observed based on the disappearance of the characteristic peaks of amino groups on FDU-HOF-1 in the Fourier transform infrared (FTIR) and solid-state nuclear magnetic resonance (ss-NMR). The variable temperature PXRD indicated the formation of a new peak at 13.2° in addition to the preservation of the original diffraction peaks of FDU-HOF-1. The water adsorption, acid-base stability (12 M HCl to 20 M NaOH) and solubility experiments concluded that the thermally crosslinked HOFs (TC-HOFs) are highly stable. The membranes fabricated by TC-HOF demonstrate the permeation rate of K+ ions as high as 270 mmol m−2 h−1 as well as high selectivity of K+/Mg2+ (50) and Na+/Mg2+ (40), which was comparable to Nafion membranes. This study provides guidance for the future design of highly stable crystalline polymer materials based on HOFs.